Organizing the pamphlet collection for effective retrieval - Teh, K.H. (University of Malaya Library, 1982)
Phamphlets are little booklets that the library receives or purchases from time to time. It is a non-periodical publication or publication not more than 48 pages.These type of collections are not easy to organise or catalogue. Describes the phamplet collection at the Medical library, UNiversity of Malaya. The collection is indexed based on the KWOC (Keyword out of context) method.